Dynamic time analysis of the influence of threat factors on the level of security of the critical infrastructure object - Яремчук, Юрій Євгенович; Салієва, Ольга Володимирівна (Ukrainian Information Security Research Journal, 2020)
Disruption of critical infrastructure (CI) can lead to emergencies that will have far-reaching negative consequences for the lives of both individual cities and the state as a whole. In this regard, the timely detection of threats and determining their impact on the level of protection of the CI object plays an important role. Given the importance of this issue, the paper proposes to conduct a dynamic analysis of the cognitive model to study the level of protection of this object. Based on dynamic causal algebra, the influence of the most important concepts of the system was determined: security of the security system and security of the computer network on security of the CI at different points in time. To achieve this goal, a vector of vertex thresholds is given, which does not depend on time and distinguishes all insignificant influences between concepts and a vector of vertex state, in which the studied vertex is activated from the outside and remains active throughout the process. Defined -wave, which generates the process of activation of the vertices and the corresponding paths. The time of stabilization of the process is set. The influences along all activated paths from the studied concepts to the target ones are calculated, on the basis of the obtained values the total influences of these concepts are determined, which are displayed graphically using the Microsoft Excel software. To automate the dynamic modeling of the analysis of the impact of concepts, a software tool has been developed that allows to reduce the time for data processing and increase the speed of their processing. After analyzing this graph, we can conclude that the security of the security system at different times has a greater impact on the security of CI than the security of the computer network, which, in turn, confirms the reliability of the results of scenario modeling.